Establishing low‐density lipoprotein apheresis tolerability in patients with prior anaphylactoid reactions to lipoprotein apheresis using magnesium sulfate. Issue 3 (18th February 2021) - Alexander, Ethan; Moriarty, Patrick M.; Wilk, Barry; Eliaz, Isaac
Abstract: Background: Lipoprotein apheresis (LA) tolerability is a key factor for the utilization of this therapy. Common reactions to LA are hypotension and nausea. Serious reactions include severe hypotension and anaphylactoid reactions (0.13%‐1.3% and 0.2%‐0.4%, respectively). The bradykinin response drives these reactions and can worsen with the use of angiotensin‐converting‐enzyme inhibitors. Efforts to mitigate these reactions are necessary for the tolerability of LA with a dextran sulfate‐adsorption (DSA) system. Materials and Methods: In an effort to increase apheresis tolerability, seven patients at The University of Kansas, Department of Clinical Pharmacology, who had prior anaphylactoid reactions (defined as general cutaneous flushing, nausea/vomiting, tongue swelling, lightheadedness, and hypotension) to the DSA despite pharmacologic intervention, were treated with pre‐LA intravenous magnesium adapted from a protocol developed by co‐author Eliaz. This protocol consists of 1.5 g of magnesium sulfate administered over 45 minutes. All seven patients were treated with intravenous magnesium sulfate immediately before LA. Results: No episodes of anaphylactoid reactions during LA have been reported to date. Conclusions: Magnesium infusion before DSA can be utilized to establish tolerability in patients with prior anaphylactoid reactions to LA. Proposed mechanisms include temporary stabilization of the negative‐positive interactions of the dextran sulfate filter leading to a reduction of circulating bradykinin, reduction of nitric oxide, and reduction of the sympathetic response to LA.